(untitled) - Freedman, Roger A. (New York, 2005)
What astronomers know about our universe changes every day. For the past twenty years, Universe has been the most thrilling way to communicate the excitement of discovery in astronomy, to students of all scientific backgrounds. The new edition of Universe gives students the means to explore like never before. In addition to covering all the top discoveries, the text contains spectacular images, captivating writing, and a media and supplements package that guides students on a fascinating journey around the cosmos and back again
Keywords: Cosmology,Vũ trụ học